From Sensing to Alerting: a Pathway of RESTful Messaging in Ambient Assisted Living - Hossain, M. Anwar (2016)
Sensing and alerting are fundamental to AAL. It is a long way from sensing to alerting, where lots of messages are interchanged among different processing units. Starting from the transfer of sensed data to the data processor and all the way to the alert generator, messages change in format, type, and size when intended for different stakeholders. Along this way, it becomes important to decide which messages to transfer, how to transfer, and when to transfer, taking into account the dependability requirements for a reliable AAL system. This article highlights AAL communication from various message transfer perspectives and proposes a general framework of alert/response in an AAL environment addressing these messaging requirements. The cornerstone of the proposed framework is the consideration of dependable RESTful communication throughout the message trail within a local and cloud-based environment. This is coupled with a publish-subscribe mechanism that offers a lightweight solution to address the variability of message transfers in AAL.